Programming Languages 18th Brazilian Symposium, SBLP 2014, Maceio, Brazil, October 2-3, 2014. Proceedings - Quintao Pereira, Fernando Magno (Programming and Software Engineering, 2014)
This book constitutes the proceedings of the 18th Brazilian Symposium on Programming Languages, SBLP 2014, held in Maceio, Brazil, in October 2014. The 11 full papers were carefully reviewed and selected from 31 submissions. The papers cover topics such as program generation and transformation; programming paradigms and styles; formal semantics and theoretical foundations; program analysis and verification; programming language design and implementation.